Effect of the nano-cellulose content on the properties of reinforced polyurethanes. A study using mechanical tests and positron annihilation spectroscopy - Aranguren, Mirta Ines (2012)
A study of the effect of the addition of cellulose nanocrystals on the properties of a polyurethane matrix was carried out. To this aim, mechanical and dynamic mechanical tests together with positron annihilation lifetime spectroscopy (PALS) were used. The rheological response of the unreacted liquid suspensions indicates strong interactions between nanocrystals and polymer, showing a viscoelastic solid-like behavior at low cellulose concentration. The study of the cured elastomers revealed a strong dependence of their properties on cellulose content, with a peculiar behavior appearing below the percolation threshold (∼0.8 wt.%). PALS studies revealed that, for the neat polyurethane and nanocomposites, the free nanohole volume value remains unchanged. Conversely, the fractional free volume is strongly dependent on nanocellulose concentration. This parameter shows very good correlation with mechanical ones (Young´s and storage moduli) related to the elastomer rigidity. Results are analyzed in terms of the interaction between the polyurethane chains that become attached to the cellulose nanocrystals through strong physical H-bonding and covalent linkages.